THE CIVIL POLITICS AND POLITICAL PARTICIPATION IN THAI SOCIETY - Chimhad, Pairat; Praekpan, Banyat; Onkong, Samit (Journal of MCU Nakhondhat, 2020)
The civil politics and political participation is a situation in which people have the right and freedom to participate in the policy process There is a decentralization for people to define their own way of life without violating the rights of others. Within the framework of the law Which any policy activities that may affect people Citizens must participate in the first place And people can conduct political activities by themselves In the Constitution of the Kingdom of Thailand, B.E. 1997, there is an important intention to change the politics of politicians into citizens’ politics by promoting the rights and freedoms of the people. People are involved in politics and government. Is a civil politics that is parallel with the politics of politicians By promoting civil politics for effectiveness Must have support to monitor and examine the political reform process. The birth of a public organization Campaign for democracy learning Raising awareness To strengthen democratic culture Involvement of citizens in the examination of elections and the exercise of state power, which requires concrete support, such as laws that promote and support political participation of citizens or civil politics so that people can Able to conduct political activities in the civil society fully, continuously, independently, with low cost and without being a burden to oneself more than necessary. It also gives people the opportunity to participate in the formulation of government policies. And is a process to measure the political development in democracy of each country Therefore, the country That developed politics and democratic governance to a good level Usually assigned to people at all levels Have the right to political participation in accordance with the law And have practical results.